Diversity of Plankton in the Part of Upstream Siak River Palas Village, Pekanbaru City, Riau Province - Rahayu, Sri; ', Efawani; ', Yuliati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study on the diversity of plankton in the part of upstream Siak River wasconducted from Mei-Juli 2013. This research aims to understand the abundance anddiversity of plankton in that area. There were three stations with 3 sampling points ineach station. Samples were taken 3 times, once a week and they were analyzed in theAquatic Ecology and Environmental Management Laboratory of the Fisheries andMarine Science Faculty, Riau University.Result shown that the phytoplankton obtained were consist of 25 species, theywere belonged to of 3 classes, namely Chlorophyceae (10 species), Bacillariophyceae(7 species), and Cyanophyceae (8 species). The average of fitoplankton abundance wasaround 1261-2540 cells/l. The most common phytoplankton was Planktonema sp.(334 cells/l, Chlorophyceae). Diversity index (H') was 2,91–3,07, equitability index (E)was 0,90–0,95 and dominancy index (C) was 0,05–0,08 and result shown that thezooplankton obtained were consist of 10 species, they were belonged to of 3 classes,namely Rotifera (5 species), Ciliata (3 species), and Copepoda (2 species). The averageof zooplankton abundance was around 414-530 inds/l. The most common zooplanktonwas Notholca sp. (88 inds/l, Rotifera). Diversity index (H') was 2,08-2,27, equitabilityindex (E) was 0,90–0,99 and dominancy index (C) was 0,11–0,12. General waterquality parameters are as follow: temperature: 29,3-30,3 0C, brightness: 30-33 cm,current speed: 0,11-0,18 m/s, pH: 5-6, DO: 3–3,4 mg/l, CO2: 8,98–10,98 mg/l, nitrate:0,11–0,14 mg/l and phosphate 0,015–0,019 mg/l. Based on plankton abundance, theSiak River can be categorized as oligotriphic river.Keywords : Plankton Abundance, Phytoplankton, Zooplankton, Upstream Siak River